Institutional activism in the early American automobile industry - Rao, Hayagreeva (Journal of Business Venturing, 2004)
A common proposition is that new industries gain constitutive legitimacy through claim making by institutional activists. Yet, neoinstitutional research seldom analyzes the effects of claim making on the formation of new organizations, and how the effect of claim making is moderated by other sources of constitutive legitimacy: advertising, legal recognition, and a policy regime favorable to business. I explore the relationship between claim making by activists and new organization building in a study of the early American automobile industry, when auto clubs organized reliability contests to validate the automobile. The results show that the visibility of reliability contests within the focal state increased foundings of car firms in the state, but that this effect diminished with advertising, legal recognition of the car, and the existence of a business friendly governor in the focal state. Taken together, these results demonstrate that claim making is crucial in the early phase of gaining legitimacy for new industries.